Product Tax Modelling in INFORGE - Anke Mönnig (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2008)
In this paper, the application of INFORGE as an analyzing tool for fiscal policy shocks is introduced by using the example of taxes on products. In recent times, variations of tax rates on product taxes have become rather popular because it is a simple method to consolidate state budget. A detailed modelling of taxes on products is important for further two reasons: (i) they are an important component for the transition from demand at purchasers' prices to demand at basic prices. (ii) Taxes on products can be classified in general and specific consumption taxes. Both tax types affect categories of goods in a different way and have to be modelled accordingly. Thus, the main objective is to describe the setting of the database as well as the modelling approach of taxes on products in INFORGE. The paper ends with a simulation example on the variation of value added tax rates.
Keywords: 330